An Infrared and Raman Spectroscopic Study of Pyrazine Cadmium II Tetracyanometalate II Benzene 1 1 Clathrates - Ekici, Nurcan; Kantarci, Ziya; AKYÜZ, SEVİM (Kluwer Academic Publishers, 1991)
Two new benzene clathrates of the form Cd(Pyrazine)M(CN)4⁗C6H6, where M = Cd or Hg, have been prepared and their infrared and Raman spectra are reported.
Keywords: Hofmann-Td-type benzene clathrate; Cd-pyrazine complex; benzene inclusion compound; IR and Raman spectra